3D ultrasonografické vysetrování pohybového aparátu - Hrazdira, L; Skotáková, J (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2006)
Three-dimensional (3D) sonography is the next logical step in diagnostic ultrasound examination. The true value of 3D ultrasonography, however, becomes evident only if 3D structures can be assessed without preconceptions ensuing from 2D interpretations. 3D ultrasonography can greatly improve our understanding of locomotor apparatus anatomy and pathology. The authors used spatial analysis to evaluate the data obtained by examination of patients with orthopedic diagnoses. The Voluson 530 MT and SONOReal system were used for examination. The Voluson permits a choice of either a 2D or a 3D imaging program for musculoskeletal system examination. The SONOReal, owing to a positional sensor of the probe, can be attached to any ultrasound transducer. In the period from 1990 to 2004, a total of 19 000 patients were examined by ultrasonography and, in 6 500 of them, the diagnosis was verified by another method, which showed a 99 % reliability of ultrasound examination. In 350 patients 2D imaging was followed by 3D examination; in 53 of them, 3D coronal and multiplanar imaging made the diagnosis based on 2D imaging more accurate and, in 12 patients, it provided new information on the patient's diagnosis. 3D reconstructions were made in 101 patients, of these 40 had been examined by other imaging methods (magnetic resonance, computer-assisted tomography) or arthroscopy. The results of examination showed a 100% correlation. Spatial reconstruction is based on the volume rendering method. This is an extension of the planar reconstruction method. Additional image processing techniques are used for a region of interest within a 3D volume data set. 3D ultrasound revealed a spatial relationship between lesions and their surfaces. The surface mode requires that the interface between tissues with different acoustic impedances should be a start line of 3D rendering. The acoustic threshold is a condition that restricts imaging circumstances in which surface rendering will be successful. Exploring 3D reconstructions with power Doppler scanning, which is more sensitive for tracking vessels, is a unique technique that can hardly be compared with any other imaging modality. 3D-volume imaging gives the examiner freedom to generate anatomical views from an infinite number of perspectives and allows us to explore anatomic relationships in the ways not available in any conventional 2D imaging. A spatial reconstruction presents a nearly perfect anatomical model. The possibility of storing volume data is considered a further progressive trend. It greatly contributes to enhancement of the scope of follow-up examinations, permits comparisons of expert conclusions and can serve educational purposes. The digital technology offers various networking solutions and plays a role in the development of 3D telemedicine. Although the diagnostic efficacy of 3D imaging is not greatly enhanced when compared with a 2D examination done by a well-trained specialist, the features of coronary sections and spatial reconstructions represent great progress of this imaging technology.
Keywords: Imaging, Three-Dimensional; Musculoskeletal System; zobrazování trojrozměrné; Ultrasonography; ultrasonografie; Humans; lidé; muskuloskeletální systém; počítačové zpracování obrazu; Image Processing, Computer-Assisted